2022
DOI: 10.1016/j.vaccine.2021.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Did the European suspension of the AstraZeneca vaccine decrease vaccine acceptance during the COVID-19 pandemic?

Abstract: On March 11, 2021, the AstraZeneca vaccine against COVID-19 was suspended in three Nordic countries and, on subsequent days, in other European countries. Using data on vaccine acceptance in eight Western countries obtained on a daily basis, we show that these decisions - and associated news - decreased public vaccine acceptance in several countries and part of this decrease happened in response to suspensions in other countries. The findings demonstrate the importance of international coordination between heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 9 publications
1
19
0
Order By: Relevance
“…The MoH's decision to suspend this vaccine after AEFIs was critically reported to be abrupt and confusing, while other articles argued it was slow and irresponsible. Similar situations with HPV vaccine in Japan, Hepatitis B vaccine in China and Astra Zeneca COVID-19 vaccine in Europe showed that a suspension policy itself can decrease public vaccine confidence 11,21,50 , negative framing of the decision in mainstream news can amplify anxiety. As the situation progressed, most subsequent articles added an explanation from the MoH in an attempt to balance the confusion.…”
Section: Discussionmentioning
confidence: 95%
“…The MoH's decision to suspend this vaccine after AEFIs was critically reported to be abrupt and confusing, while other articles argued it was slow and irresponsible. Similar situations with HPV vaccine in Japan, Hepatitis B vaccine in China and Astra Zeneca COVID-19 vaccine in Europe showed that a suspension policy itself can decrease public vaccine confidence 11,21,50 , negative framing of the decision in mainstream news can amplify anxiety. As the situation progressed, most subsequent articles added an explanation from the MoH in an attempt to balance the confusion.…”
Section: Discussionmentioning
confidence: 95%
“…Even after the positive verdict of the European Medicines Agency (EMA) eight days after the stop, the climate of uncertainty [ 19 ] continued to impact on the vaccination campaign, leading to the phenomenon of vaccine hesitation. This meant reluctance, delay and indecision about being vaccinated out of fear of having adverse reaction to the shot, eventually leading to increased distrust about vaccines and pharmaceutical regulation institutions.…”
Section: Resultsmentioning
confidence: 99%
“…48 Furthermore, ChAdOx1-S [recombinant] was initially widely distributed due to less restrictive storage conditions, but the safety concerns amplified rumors and led to lower uptake. 49 Hence, only eight African countries managed to use their received COVAX doses, nine nations administered less than a quarter of their doses, and 15 nations administered less than half of the received COVID-19 doses, according to WHO.…”
Section: Discussionmentioning
confidence: 99%